2015
DOI: 10.1515/jpem-2014-0472
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and molecular characterization of five Spanish kindreds with X-linked adrenal hypoplasia congenita: atypical findings and a novel mutation in NR0B1

Abstract: AHC phenotype cannot be predicted based on genetic results as there is no definite genotype-phenotype relationship, including intrafamilial variability. Nevertheless, genetic testing for NR0B1 mutations is indicated if there is a suspicion of an X-linked adrenal insufficiency in order to proceed with the appropriate therapy and genetic counseling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…HH is the most common finding [1,24]. However, delayed or incomplete puberty associated with partial gonadotropin deficiency [1,26,27] or phenotypes with normal gonadotropin function have also been described [12,14,[28][29][30][31]. More puzzling, some have suggested that chronic ACTH stimulus to Leydig cells may be related to gonadotropin-independent precocious puberty phenotype in X-linked AHC boys [28].…”
Section: Discussionmentioning
confidence: 99%
“…HH is the most common finding [1,24]. However, delayed or incomplete puberty associated with partial gonadotropin deficiency [1,26,27] or phenotypes with normal gonadotropin function have also been described [12,14,[28][29][30][31]. More puzzling, some have suggested that chronic ACTH stimulus to Leydig cells may be related to gonadotropin-independent precocious puberty phenotype in X-linked AHC boys [28].…”
Section: Discussionmentioning
confidence: 99%
“…Frameshift and non-sense mutations may occur within the entire open reading frame, while missense mutations are found mainly in the region encoding the C-terminus of the DAX1 protein (22,25). Other pathogenic alterations comprise copy-number variations (CNVs) of different sizes (26). In patient 6, AHC was caused by a pathogenic deletion encompassing the entire exon 2 of DAX1, which has not been reported before.…”
Section: Genetic Causes For Pai Case Seriesmentioning
confidence: 87%